Effect of high temperature corrosion on austenitic stainless steel grade 304 in CO2 gas at 700ºC - Nurul Atikah Shariff; Azman Jalar; Muhamad Izhar Sahri; Norinsan Kamil Othman (Universiti Kebangsaan Malaysia, 2014)
Austenitic stainless steels of grade 304 were exposed to dry (Ar-75%CO2) and wet (Ar-75%CO2-12%H2O) environments at 700oC. This experimental setup involved horizontal tube furnace connected to CO2 gas and water vapour facilities. X-ray diffraction (XRD) technique, variable pressure-scanning electron microscope (VP-SEM) and optical microscope techniques were used to characterize the products of corrosion. The results of XRD showed that the phase of oxide layers consists of Cr2O3 and NiCr2O4 in dry CO2, meanwhile Fe2O3, Cr2O3, Fe0.56Ni0.34, Fe3O4 were identified in wet condition after 50 h. Adding 12%H2O in Ar-75%CO2 leads significantly in weight change occurred at 10 h exposure. However, after 20 h, the weight gain was decreased due to spallation of the oxide scale. The addition of water vapour accelerates the oxidation rate on the steel than that in dry condition. Morphologies and growth kinetics of these oxides vary with reaction condition. The oxidation behaviour at different times of exposure and the effect of water vapour were discussed in correlation with the microstructure of the oxides.